Economic Competence and Financial Literacy of Young Adults Status and Challenges - Wuttke, Eveline; Seifried, Jürgen; Schumann, Stephan (Research in Vocational Education, 2016)
The authors take a detailed look at the economic competence and financial literacy of young adults, especially of those who start an apprenticeship or who take up their studies at a university. Economic competence and financial literacy are of special interest within this group, because these young people are - mostly for the fi rst time in their lives - responsible for autonomously managing their own fi nancial affairs and deal with economic challenges.